Evaluation of the Catalonian Parliament, 1980-1984 - Carreras, Francesc; Owen, Guillermo (Monterey, California. Naval Postgraduate School, 1986)
We analyze here the process of coalition formation in the Catalonian Parliament. Using Owen's modification of the Shapley Value (for games with a Priori Unions), we show that the actual result is not unreasonable, given the underlying political structure. NA Prepared for: Naval Postgraduate School Monterey, CA http://archive.org/details/evaluationofcata00carr